Tindak Pidana Persetubuhan Yang Dilakukan Secara Paksa Terhadap Anak (Putusan Nomor 119/Pid.B/2021/PN AMB) - Wado, Riska La Ode; Sopacua, Margie Gladies; Fadillah, Astuti Nur (Faculty of Law Universitas Pattimura, 2023)
This research discusses the application of material criminal law and criminal responsibility for perpetrators of criminal acts of sexual intercourse committed by force against children in this case. Purposes of The Research to analyze and discuss the application of material criminal law as well as examine and analyze criminal liability for perpetrators of criminal acts of sexual intercourse committed by force against children. Methods of The Research the research method used is normative juridical research. This research uses three problem approaches, namely the statutory approach, the conceptual approach and the case approach. The data sources obtained are primary legal materials and secondary legal materials. The technique for collecting legal materials uses the literature study method. All data in this study were analyzed qualitatively. Results of The Research the results of this research show that, in examining criminal cases, judges try to find and prove material truths based on the facts revealed in the trial, and stick to what is formulated in the public prosecutor's indictment. The element of unlawfulness is one of the parameters in determining personal responsibility for personal mistakes committed by the perpetrator. The perpetrator of the crime of sexual intercourse in this case has fulfilled the elements of the charges charged by the Public Prosecutor and therefore the perpetrator must be held accountable for his actions. The judge's legal considerations were in accordance with existing regulations by considering aggravating circumstances as well as mitigating circumstances based on the legal facts discovered in the trial.